Borys Liatoshynsky’s Opera The Golden Hoop: History, Versions, Primary Sources - Iryna TUKOVA; Tetiana HOMON (Studia Universitatis Babeş-Bolyai. Musica)
The opera The Golden Hoop (1929, Op. 23) by preeminent Ukrainian composer Borys Liatoshynsky (1895–1968) is one of the most celebrated compositions in Ukrainian music history. The opera’s libretto, written by Yakiv Mamontov (1888–1940) in Ukrainian, is based on Ivan Franko’s (1856–1916) historical novel Zakhar Berkut. The Ukrainian ancient beautiful and tragic love story of Maxim and Myroslava is framed by a larger-scale narrative of great love for the Motherland and one’s compatriots. The opera exists in three versions — the initial 1929 Ukrainian version; the second Ukrainian version from the mid-1960s; and an additional Moscow version dating back to 1930. This article is the first research document that 1) examines the primary sources relating to the history of creation and staging of the first Ukrainian version of The Golden Hoop; 2) investigates the differences between the first Ukrainian and the Moscow versions; and 3) explores the modifications of the first Ukrainian version of the opera as reflected in its second, 1960s version.